T-2 toxin induces gut and liver injury through triggering gut microbiota dysbiosis - An, Keying; Yan, Dan; Lv, Xueze; Liu, Yanhan; Xia, Zhaofei (Poultry science, 2025)
T-2 toxin (T-2), a foodborne mycotoxin, causes gut and liver injury in organisms. However, its effects on intestine in ducks and the mediating role of gut microbiota in pathogenesis remain unclear. This study investigated the involvement of gut microbiota in T-2-induced enterotoxicity and hepatotoxicity in ducks. Thirty 1-day-old ducklings were divided into control (CON) and T-2-exposed (400 μg/kg BW/day via oral gavage) groups for two weeks. Alterations in gut microbiota composition and barrier function were assessed. To further elucidate the role of microbiota, antibiotics mixture (ABX) treatment and fecal microbiota transplantation (FMT) were employed. Results revealed that T-2 exposure induced ileal dysbiosis characterized by increased relative abundance of Firmicutes, Candidatus Arthromitus, and Lactococcus, decreased Corynebacterium abundance with diminished α-diversity. For gut physical barrier function, ileal villi heights and mRNA levels of mucin2, Occludin, zonula occludens-1 were significantly downregulated by T-2, and serum concentration of lipopolysaccharide was increased. Notably, ABX treatment prevented T-2-induced gut barrier disruption, completely suppressed hepatic inflammation via toll-like receptor 4 (TLR4) pathway inhibition. Hepatic lipid accumulation induced by T-2 was significantly attenuated by ABX treatment. Furthermore, FMT confirmed the essential role of T-2-altered microbiota in recapitulating pathological features including intestinal leakage, hepatic inflammation and steatosis, and upregulated TLR4 pathway and lipid metabolism genes (angiopoietin-like 4, carnitine palmitoyltransferase 1B, perilipin 1) expression. These findings establish gut microbiota as a critical mediator in T-2-induced multiorgan toxicity, providing new insights into the potential therapeutic strategies.